2016
DOI: 10.1111/ppl.12476
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Proteomic and physiological responses of Arabidopsis thaliana exposed to salinity stress and N‐acyl‐homoserine lactone

Abstract: To evaluate the alleviating action of exogenous N-acyl-homoserine lactones (AHLs) on NaCl toxicity, morphological, physiological and proteomic changes were investigated in Arabidopsis thaliana seedlings. Salinity stress decreased growth parameters, increased malondialdehyde (MDA) contents and antioxidant enzymes such as superoxide dismutase (SOD), guaiacol peroxidase (POD) and catalase activities. Application of lower concentration of AHL had a relieving effect on Arabidopsis seedlings under salinity stress wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 76 publications
1
13
0
2
Order By: Relevance
“…The subtle effects of the fip1‐2 mutation on poly(A) site choice belie the more dramatic phenotypes seen in the mutant, such as the diminished capacity to develop LRs, leaf growth, the tolerance to salt, and the increased sensitivity to cadmium and ABA. Transcriptomic and proteomic analyses have identified a large number of genes/proteins involved in root development and the adaptation of plants to salt stress or ABA responses (Brady et al ., , ; Dinneny et al ., ; Li et al ., ; Guo et al ., ; Ding et al ., ; Kumar et al ., ). It is possible that among the numerous changes in poly(A) site choice that are seen in the fip1‐2 mutant, some of them affect important regulatory genes, which might have a large impact on plant development and responses; however, our results (Figure ) suggest an interesting alternative.…”
Section: Discussionmentioning
confidence: 99%
“…The subtle effects of the fip1‐2 mutation on poly(A) site choice belie the more dramatic phenotypes seen in the mutant, such as the diminished capacity to develop LRs, leaf growth, the tolerance to salt, and the increased sensitivity to cadmium and ABA. Transcriptomic and proteomic analyses have identified a large number of genes/proteins involved in root development and the adaptation of plants to salt stress or ABA responses (Brady et al ., , ; Dinneny et al ., ; Li et al ., ; Guo et al ., ; Ding et al ., ; Kumar et al ., ). It is possible that among the numerous changes in poly(A) site choice that are seen in the fip1‐2 mutant, some of them affect important regulatory genes, which might have a large impact on plant development and responses; however, our results (Figure ) suggest an interesting alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Early investigations of the effect of AHL applications on plant development and systemic resistance have focussed on in vitro and pot-plant experiments and reported changes in gene expression patterns, root development and systemic resistance [15-16, 28-32]. In this study, we were interested in determining whether bacterial AHLs can be used as a novel class of phyto-stimulator seed primers to improve cereal crop growth and grain yields, using winter wheat to investigate changes in seed germination in vitro and field trials to investigate changes in plant development and crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigate the effect of AHL applied directly to seeds before germination whereas previous research has focused on dosing or spaying seedlings or even older plants with AHL solutions [15-16, 30-32, 39-40]. We test here the effectiveness of seed priming with C6-HSL on two varieties of winter wheat as we expected to see a strong genetic effect in response to AHL treatment, but variety effects were seen in less than half of the characteristics we measured.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of Vitis vinifera with Bacillus licheniformis Rt4M10 increased ABA concentrations in leaves (fresh weight) by 76-fold and inoculation with Pseudomonas fluorescens Rt6M10 resulted in ABA increasing by 40-fold; rates of water loss were also reduced in correlation with the increases of ABA in PGPRinoculated V. vinifera (Salomon et al 2014) The products of PGPRs which specifically induce abiotic resistance or tolerance are not as well described in the literature as those known to be involved in defense priming, but likely overlap with those found to promote plant nutrition and biotic resistance. Indeed, reported examples of abiotic resistance elicitors include PGPR products such as ACC deaminase (Glick et al 2007), phytohormones such as IAA (Marulanda et al 2009), signal molecules such as LCOs (Subramanian et al 2016) and AHLs (Ding et al 2016), and BVCs (Liu and Zhang 2015). Promising recent research into the role of PGPR BVCs on Arabidopsis salinity tolerance has shown that the Paraburkholderia phytofirmans P s J N B V C s 2 -u n d e c a n o n e , 7 -h e x a n o l , 3methylbutanol and dimethyl disulfide (DMDS) stimulated positive plant growth under both normal and saline-stress conditions (Ledger et al 2016).…”
Section: Diverse Pgpr Molecules Elicit Plant Defensementioning
confidence: 99%